Pengaruh Inflasi dan Pertumbuhan Ekonomi terhadap Tingkat Pengangguran dengan Variabel Intervening Indeks Pembangunan Manusia (IPM) di Provinsi Sumatera Barat - Husnul, Padlin; Mailindra, Wiyan; Bustami, Alex Wissalam (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the effect of inflation, economic growth and the human development index (HDI) on the unemployment rate in West Sumatra Province. The data used in this research are data on inflation, economic growth, unemployment rates and HDI for the 2014-2023 period obtained from the Central Statistics Agency (BPS). The method used is quantitative descriptive using multiple regression analysis. The research results show that partially and simultaneously the variables inflation, economic growth and HDI have no significant effect on the unemployment rate variable in West Sumatra Province.